Determination of Sun Protection Factor and Total Phenolic Content of Extract and Fraction of Matoa Leaves (Pometia pinnata) - Aini, Sindhi Hurul; Sabrina, Naya; Lestari, Siti Marwah; Soleha, Rahmatus (Tropical Biopharmaca Research Center, IPB University, 2025)
Matoa leaves (Pometia pinnata J.R. & G. Forst) are known to contain phenolic compounds with potential as natural sunscreen agents due to their ultraviolet (UV) absorption capabilities. The presence of conjugated double bonds or aromatic rings in these compounds allows absorption in the 200–400 nm wavelength range, making them suitable candidates for photoprotection. This study aimed to evaluate the sun protection factor (SPF)—a measure of a substance’s ability to protect the skin against UVB radiation—and total phenolic content of the extract and fraction derived from matoa leaves. Extraction was performed using Soxhlet apparatus with 70% ethanol, followed by liquid–liquid partitioning to obtain fractions. Total phenolic content was determined using the Folin–Ciocalteu method, while SPF was evaluated using a UV–Vis spectrophotometer in the 290–320 nm range at 5 nm intervals. The total phenolic contents of the ethanolic extract and ethyl acetate fraction were 50.51 ± 0.18 mg GAE/g and 39.27 ± 0.09 mg GAE/g, respectively. The SPF values were 19.60 ± 0.11 for the ethanolic extract and 16.37 ± 0.80 for the ethyl acetate fraction. These findings suggest that the extract and fraction of matoa leaves exhibit SPF values within the ultra-protection category, indicating their potential as natural sunscreen agents.